2014
DOI: 10.1590/s2317-643120140003000015
|View full text |Cite
|
Sign up to set email alerts
|

Teleaudiologia: comunicação profissional-paciente na programação e adaptação de aparelhos de amplificação sonora individuais via teleconsulta

Abstract: Purpose: To evaluate if teleconsultation affects professional-patient communication as well as patient satisfaction with the care for the hearing aid programming and fitting compared to the face to face consultation. Methods: Forty hearing aid candidates aged over 18 years with symmetrical sensorineural hearing loss ,from mild to severe degrees, were randomly divided into two groups: control (face to face) and experimental (synchronous teleconsultation assisted by a facilitator).Consultations were filmed, time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Others report that patients are open to telehealth consultations, but retain a preference for face-to-face services (Eikelboom et al 2014;Eikelboom and Atlas 2005;Tao et al 2020). There was a strong recognition amongst audiologists that telehealth services can lead to better efficiency: less travel for clients or clinicians, more timely attention, and better overall access, as evidenced in the audiology (Saunders and Roughley 2020;Reginato and Ferrari 2014) and broader literature (Kokesh, Ferguson, and Patricoski et al 2011;Caffery, Farjian, and Smith 2016;Taylor et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Others report that patients are open to telehealth consultations, but retain a preference for face-to-face services (Eikelboom et al 2014;Eikelboom and Atlas 2005;Tao et al 2020). There was a strong recognition amongst audiologists that telehealth services can lead to better efficiency: less travel for clients or clinicians, more timely attention, and better overall access, as evidenced in the audiology (Saunders and Roughley 2020;Reginato and Ferrari 2014) and broader literature (Kokesh, Ferguson, and Patricoski et al 2011;Caffery, Farjian, and Smith 2016;Taylor et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…HA programming, counselling, and instructions) (reviewed in Tao et al 2018;Angley, Schnittker, and Tharpe 2017), comparison of these results is difficult. The closest studies of teleaudiology services have been those examining real ear measurements (Campos and Ferrari 2012;Pross, Bourne, and Cheung 2016), counselling programme Rubinstein 1994, 1995;Laplante-Levesque, Pichora-Fuller, and Gagne 2006;Lundberg, Andersson, and Lunner 2011;Thoren et al 2011;Thoren et al 2014), and of specific procedures performed by teleaudiology but in isolation from the other procedures (Tao et al 2018;Ferrari 2006;Ferrari and Bernardez-Braga 2009;Reginato and Ferrari 2014;Campos and Ferrari 2012;Pearce, Ching, and Dillon 2009;Penteado et al 2012Penteado et al , 2014Venail et al 2019). None of these were implementation studies or compared the outcomes of remote to face-to-face follow-up services, nor was there assistance of a trained facilitator.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, significant differences were observed between private and public sector services; respondents working in publicly funded settings tended to report more positive attitudes towards teleaudiology than those from private work settings. A study by Reginato and Ferrari (2014) found that despite some aspects of clinicianpatient communication being affected by teleaudiology delivery, patient satisfaction was not adversely impacted in comparison with in-person service delivery (Reginato and Ferrari 2014).…”
Section: Introductionmentioning
confidence: 99%